2009
DOI: 10.1016/s1098-3015(10)73709-8
|View full text |Cite
|
Sign up to set email alerts
|

Prs46 Assessing Asthma Management in an Urban Community in Delhi, India

Abstract: Background & objectives:High prevalence and poor control of asthma make its management a major public health issue worldwide, especially in developing countries. Optimum review of asthma management in the community is essential to improve asthma control. This study was conducted to investigate the quality of asthma management, knowledge about asthma and quality of life of asthma patients referred to a public tertiary care chest hospital in Delhi.Methods:Diagnosis of asthma was confirmed by symptoms and reversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Although a part of our definition of asthma was similar to Aggarwal et al, we also included additional symptomatic definition of the disease which was derived from various asthma epidemiological studies [20,21]. We assume that relying only on physician diagnosis of asthma in an epidemiological surveys, although specific, can induce a risk of underestimating a disease in community especially when there is poor understanding of a disease even at the physician level [26]. This could be the reason of low prevalence reported in study by Aggarwal et al, and has falsely placed India in low asthma prevalence zone globally.…”
Section: Discussionmentioning
confidence: 99%
“…Although a part of our definition of asthma was similar to Aggarwal et al, we also included additional symptomatic definition of the disease which was derived from various asthma epidemiological studies [20,21]. We assume that relying only on physician diagnosis of asthma in an epidemiological surveys, although specific, can induce a risk of underestimating a disease in community especially when there is poor understanding of a disease even at the physician level [26]. This could be the reason of low prevalence reported in study by Aggarwal et al, and has falsely placed India in low asthma prevalence zone globally.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indicated that asthma management and pharmacotherapy is not optimal in the community setting within urban India [16-18]. A recent study showed that asthma patients referred to hospital and treated with pharmacotherapy according to standard treatment guidelines demonstrated improvement in various parameters of asthma control within 2-8 weeks [19].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the revolutionary changes in asthma management the morbidity and mortality due to asthma is increasing worldwide 1 . Prevalence of asthma is over 3.5% in adults and over 5.1% in children in our country and the burden is constantly increasing 4 . Asthma is a chronic inflammatory disorder characterized with the intermittent and variable periods of airway obstruction.…”
Section: Introductionmentioning
confidence: 97%